REGULATION OF FIREARM OWNERSHIP FOR CIVILIANS IN INDONESIA BASED ON THE PRINCIPLE OF SELF-DEFENSE IN THE LEGAL PROTECTION SYSTEM (STUDY OF THE REPUBLIC OF INDONESIA LAW NUMBER 8 OF 1948 ON THE REGULATION OF THE INDONESIAN NATIONAL POLICE CHIEF NUMBER 82 OF 2004 - Asmariah Asmariah; Sukamto Kusnadi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The need for legal protection for every human being is an undeniable matter. It is crucial to ensure that every citizen feels safe, and one of the efforts made by individuals to achieve this sense of security is by owning firearms. In the prevailing laws and regulations, civilians are allowed to possess firearms (firearms) as self-defense tools to protect themselves. In Indonesia, the law of self-defense is regulated in the Criminal Code (KUHP) Article 49. The following is an excerpt from Article 49 KUHP: "Any person who, due to necessity, takes necessary action to defend themselves, others, or their property from an attack that threatens lives, endangers themselves, others, or their property, shall not be punished." This article states that a person cannot be punished if they take necessary action to defend themselves, others, or their property from an attack that threatens lives or endangers themselves, others, or their property, but the action must be forced and necessary in the situation they face. The possession of firearms must comply with the requirements and provisions set by the Indonesian National Police (Polri). According to Perkap No. 82 of 2004, civilian individuals who wish to own firearms are limited to certain groups, such as CEOs, ministers, government officials, major entrepreneurs, commissioners, lawyers, and doctors. This consideration takes into account the urgency and risks that these professional holders may face. The regulation also states that firearm ownership cannot be granted to just anyone. Those who want to apply for a firearm ownership permit must have shooting skills. Prospective firearm owners are required to have shooting skills for a minimum of three years. Additionally, they must fulfill various requirements, including psychotest and medical tests.